Penyuluhan Kelancaran Saluran Drainase di Desa Muara Uwai Kecamatan Bangkinang - Febryanto; Setiawan, Beny; Saputra, Azlan (Journal of Social and Community Service, 2025)
This community service activity was conducted in Muara Uwai Village, Bangkinang District, Kampar Regency, with the aim of increasing public understanding and awareness of the importance of drainage channels in supporting environmental sustainability and flood prevention. The main challenges faced by the community were low awareness of the function of drainage, lack of knowledge in maintenance, and inadequate infrastructure. Implementation methods included field surveys, outreach, outreach, and the provision of educational materials in the form of brochures and group discussions. The results of the activity demonstrated an increase in community understanding of how to independently maintain and repair drainage channels, as well as a growing awareness of the importance of keeping the environment clean and free from waste that can clog the channels. Active community participation in this activity is an indicator of success and opens up opportunities for ongoing collaboration between the village government, residents, and universities. This program is expected to serve as a model for community empowerment in sustainable drainage management and support the creation of a healthy, flood-free village environment.